2022
DOI: 10.3390/ijms232314520
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation of SIRT1 Protects against Cold Stress-Induced Skeletal Muscle Damage via Amelioration of Mitochondrial Homeostasis

Abstract: Cold stress disturbs cellular metabolic and energy homeostasis, which is one of the causes of stress-induced illnesses. O-GlcNAcylation is a nutrient-sensing pathway involved in a myriad of cellular processes. It plays a key role in metabolic homeostasis. Nevertheless, a specific sensing mechanism linking skeletal muscle to O-GlcNAcylation in cold stress is unknown. In this study, O-GlcNAcylation of SIRT1 was targeted to explore the mechanism of skeletal muscle adaptation to cold stress. Ogt mKO aggravated ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…OSMI-1 significantly increased ROS-induced endoplasmic reticulum (ER) stress, resulting in a decrease in Bcl2 and the release of cytochrome c from mitochondria [92]. Deletion of the OGT gene aggravated the homeostatic imbalance and oxidative stress in mitochondria induced by cold stress in skeletal muscle [93]. Jóźwiak et al reported that the increased expression of mOGT affects the mitochondrial transmembrane potential and increases the production of mROS.…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…OSMI-1 significantly increased ROS-induced endoplasmic reticulum (ER) stress, resulting in a decrease in Bcl2 and the release of cytochrome c from mitochondria [92]. Deletion of the OGT gene aggravated the homeostatic imbalance and oxidative stress in mitochondria induced by cold stress in skeletal muscle [93]. Jóźwiak et al reported that the increased expression of mOGT affects the mitochondrial transmembrane potential and increases the production of mROS.…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…O‐GlcNAcylation of SIRT1 ( Figure ) acts to define its spatiotemporal distribution between the nucleus and cytoplasm, and thus, its functionality, 65 and conversely, SIRT1 and NAD+ (the primary driver of SIRT1 activity) act to diminish O‐GlcNAcylation through inhibition of OGT 66,67 . During states of acute stress, O‐GlcNAcylation of SIRT1 enhances its ability to reduce cellular apoptosis 68,69 . In contrast, during nutrient surplus, O‐GlcNAcylation of SIRT1 reduces its interactions with PGC‐1α and promotes its nuclear exclusion and proteosomal degradation 65 .…”
Section: Interaction Of Udp‐glcnac With Other Nutrient‐sensitive Sign...mentioning
confidence: 99%
“…64 O-GlcNAcylation of SIRT1 (Figure 3) acts to define its spatiotemporal distribution between the nucleus and cytoplasm, and thus, its functionality, 65 and conversely, SIRT1 and NAD+ (the primary driver of SIRT1 activity) act to diminish O-GlcNAcylation through inhibition of OGT. 66,67 68,69 In contrast, during nutrient surplus, O-GlcNAcylation of SIRT1 reduces its interactions with PGC-1α and promotes its nuclear exclusion and proteosomal degradation. 65 Enhanced glucose entry and O-GlcNAcylation suppresses the expression of PGC-1α 70 and negates the actions of PGC-1α to promote the use of ketone bodies as a myocardial fuel.…”
Section: Interplay Of O-glcnacylation and Nutrient Deprivation Sensor...mentioning
confidence: 99%
“…105 During states of acute stress, O-GlcNAcylation of SIRT1 enhances its effects on organellar and cellular health. 106,107 By contrast, during nutrient surplus states seen in chronic stress, O-GlcNAcylation of SIRT1 promotes its nuclear exclusion and proteosomal degradation. 104 At the same time, there is an intimate interplay between UDP-GlcNAc and PI3K/AKT/mTOR because both are upregulated by nutrient surplus (Figure 2).…”
Section: Protein Modification By O-glcnacylationmentioning
confidence: 99%
“…105 During states of acute stress, O-GlcNAcylation of SIRT1 enhances its effects on organellar and cellular health. 106,107 By contrast, during nutrient surplus states seen in chronic stress, O-GlcNAcylation of SIRT1 promotes its nuclear exclusion and proteosomal degradation. 104…”
Section: O-glcnacylation By Uridine Diphosphate N-acetylglucosaminementioning
confidence: 99%